THE INFLUENCE OF SUSTAINABILITY REPORT DISCLOSURE, GREEN ACCOUNTING, AND COMPANY SIZE ON THE QUALITY OF FINANCIAL REPORTS - Nurfaidah Nurfaidah; Agus Umar Gazali; Rusdiah Rusdiah; Bunyamin Bunyamin; Andi Hadidu; Syamsul Bahri (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
This study aims to evaluate the influence of Sustainability Report Disclosure, Green Accounting, and Company Size on the Quality of Financial Reports. The research involves a sample comprising non-primary and primary consumer companies in the energy, basic materials, raw materials, and non-cyclical consumer sectors during the period 2020-2022. The data under analysis is sourced from secondary data acquired through the official website www.idx.co.id or company websites, using purposive sampling as the sampling method. Research testing is conducted through multiple regression analysis. In this investigation, Sustainability Reports adhere to the guidelines of the Global Reporting Initiative (GRI) 2016, covering economic, social, and environmental performance. The aim of presenting sustainability reports is to instill public trust and confidence among various stakeholders, indicating that the company prioritizes not only profit but also environmental concerns. Companies issuing Sustainability Reports are believed to create a positive impression on consumers, serving as evidence of corporate responsibility to shareholders and compliance with relevant regulations. Green Accounting is integrated into the Sustainability Report, while Company Size is measured by the total assets of the company. The study findings reveal that Sustainability Reports and Green Accounting positively impact the Quality of Financial Reports, whereas Company Size exerts a negative influence on the Quality of Financial Reports.